Alcohol ban during the COVID-19 pandemic lockdown: Lessons for preventing foetal alcohol spectrum disorder in South Africa - Babatope O. Adebiyi; Ferdinand C. Mukumbang (AOSIS, 2022)
During the two national lockdowns implemented in South Africa to curb the spread of the coronavirus disease 2019 (COVID-19) pandemic, the sale and consumption of alcoholic beverages were prohibited. There is observational evidence from the literature suggesting a drastic reduction in the emergency and trauma unit admissions in many South African hospitals and clinics with alcohol-related restrictions. This article explores the potential benefits of the restrictions placed on the sale and consumption of alcohol during the COVID-19 pandemic on preventing foetal alcohol spectrum disorder (FASD) in South Africa. Following the potential benefits of the alcohol bans, we recommended that the current South African national liquor policy and the 2012 South African government-drafted Bill for Control of Marketing of Alcoholic Beverages should be fully implemented and enforced. Furthermore, the 'best buys' by the World Health Organization (WHO) should be adapted (based on local evidence) and executed. Implementing the abovementioned policies can reduce alcohol abuse by limiting and regulating the manufacturing, distribution, advertising, sponsorship, promotion, physical availability and hours of sale of alcoholic beverages in South Africa. Contribution: This article shows that alcohol bans during the coronavirus disease 2019 (COVID-19) lockdown reduced the short-term effects of alcohol. We believe that this could be a game-changer for the prevention of FASD in South Africa and positively impact the incidence and prevalence of FASD. This piece provides evidence that policymakers, health practitioners and academics can use to continue advocating for stricter alcohol control measures in South Africa.